Pernikahan Poligami Di Wilayah Administrasi Kantor Urusan Agama Kecamatan Playen Tahun 2012-2015 - Asmorohadi Asmorohadi (Universitas Cokroaminoto Yogyakarta, 2018)
The Office of Religious Affairs (KUA) of Playen District in Gunungkidul Regency has conducted polygamous marriages from 2012-2015 with the permission of the Religious Courts. From there it can be identified the reasons for polygamy and judges' consideration in it to find out the growing marital conditions in the region. This qualitative research method of data collection was carried out with documentation of various marriage documents and interviews with KUA Playen District, Gunungkidul Regency